Isolated Testicular Relapse of Acute Myeloid Leukemia (AML) after Allogeneic Stem Cell Transplantation (ASCT): A Case Report - Sinha, Bipasha; Sutradhar, Arpita; Bhattacharya, Debmalya (Annals of Pathology and Laboratory Medicine, 2025)
Allogenic Stem Cell Transplant (ASCT) is thought to be curative for patients with acute leukemia. Extramedullary relapse after ASCT is a cause for concern, as it usually precedes bone marrow relapse and can result in treatment failure and high mortality rates. The testis is an immune-privileged site, and relapse at this site is rare in AML. Here, we present a case of AML in a patient who had achieved complete remission and undergone ASCT, and who presented with testicular pain a year later. He was diagnosed with testicular relapse and subsequently with involvement of the cerebrospinal fluid (CSF), while his peripheral blood and bone marrow were negative for blasts and free from disease.